Arctic moisture source for Eurasian snow cover variations in autumn - Wegmann, Martin; Orsolini, Yvan; Vázquez, Marta; Gimeno, Luis; Nieto, Raquel; Bulygina, Olga; Jaiser, Ralf; Handorf, Dörthe; Rinke, Annette; Dethloff, Klaus; Sterin, Alexander; Brönnimann, Stefan (Environmental Research Letters, 2015)
Eurasian fall snow cover changes have been suggested as a driver for changes in the Arctic Oscillation and might provide a link between sea-ice decline in the Arctic during summer and atmospheric circulation in the following winter. However, the mechanism connecting snow cover in Eurasia to sea-ice decline in autumn is still under debate. Our analysis is based on snow observations from 820 Russian land stations, moisture transport using a Lagrangian approach derived from meteorological re-analyses. We show that declining sea-ice in the Barents and Kara Seas (BKS) acts as moisture source for the enhanced Western Siberian snow depth as a result of changed tropospheric moisture transport. Transient disturbances enter the continent from the BKS region related to anomalies in the planetary wave pattern and move southward along the Ural mountains where they merge into the extension of the Mediterranean storm track.